Gender Difference in Household Consumption: Some Convergence over Three Decades - O'Donoghue, Cathal; Doorley, Karina; Sologon, Denisa (The Economic and Social Review, 2024)
The cost-of-living crisis has increased attention on consumption and how it differs for particular societal groups. There is much theoretical evidence that consumption patterns of men and women should differ, but the empirical evidence is scant, due in part to the availability of individual level consumption data. This paper tackles the question of consumption differentials between men and women over nearly three decades in Ireland. Using harmonised survey data, we show how patterns of consumption of male- and female-headed households have changed over this period of significant economic turmoil and growth.